Planning a Timetable for Deciding to Registration in Course - Kruesri, Supapich; Thongkamton, Phatthawarin; Sudawan, Manisa; Youngnoi, Rawin (Journal of Science Ladkrabang, 2025)
The manual scheduling of university courses is a complex and challenging process due to the diverse registration requirements across academic programs. This research investigates the University Course Timetabling Problem (UCTP) by applying Integer Programming Problem (IP) models to construct mathematical formulations for solving optimization problems and managing intricate constraints. The primary objective is to propose a systematic course registration methodology and develop timetables that enable students to complete their academic programs in the shortest possible duration. The findings reveal that the proposed timetable planning approach effectively reduces scheduling complexity and facilitates students’ timely completion of their courses. This study provides a guideline for course registration. However, class scheduling should also consider additional factors to ensure appropriate and individualized decision-making.